2013
DOI: 10.1186/1479-5876-11-41
|View full text |Cite
|
Sign up to set email alerts
|

High intratumoral metastasis-associated in colon cancer-1 expression predicts poor outcomes of cryoablation therapy for advanced hepatocellular carcinoma

Abstract: BackgroundCryoablation is one of the local therapies for hepatocellular carcinoma (HCC), but its safety and effect has not been studied in patients with Child class A or B and Barcelona Clinic Liver Cancer (BCLC) stage C HCC. Metastasis-associated in colon cancer-1 (MACC1) overexpression has been associated with poor prognosis of HCC, but its predictive value to post-cryoablation outcomes remains unknown in patients with BCLC stage C HCC.MethodsThis study assessed the safety and outcomes of cryoablation measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…10 A total of 120 patients with Child-Pugh class A or B cirrhosis and advanced BCLC stage C unresectable HCC underwent cryoablation. 46 The median TTP and OS were 5.5 (4.2 to 6.7) and 10.5 (9.0 to 12.0) months, respectively, which were comparable with the previously reported TTP and OS rates when using RFA 49 or sorafenib therapy. 50 Clearly, above recent studies, especially the larger study by Yang et al 10,46 strongly support the clinical benefits and indications of cryotherapy for treating HCC, including advanced stage of HCC, in patients with ChildPugh class A or B cirrhosis.…”
Section: Cryoablation For Hccsupporting
confidence: 86%
See 2 more Smart Citations
“…10 A total of 120 patients with Child-Pugh class A or B cirrhosis and advanced BCLC stage C unresectable HCC underwent cryoablation. 46 The median TTP and OS were 5.5 (4.2 to 6.7) and 10.5 (9.0 to 12.0) months, respectively, which were comparable with the previously reported TTP and OS rates when using RFA 49 or sorafenib therapy. 50 Clearly, above recent studies, especially the larger study by Yang et al 10,46 strongly support the clinical benefits and indications of cryotherapy for treating HCC, including advanced stage of HCC, in patients with ChildPugh class A or B cirrhosis.…”
Section: Cryoablation For Hccsupporting
confidence: 86%
“…46 The median TTP and OS were 5.5 (4.2 to 6.7) and 10.5 (9.0 to 12.0) months, respectively, which were comparable with the previously reported TTP and OS rates when using RFA 49 or sorafenib therapy. 50 Clearly, above recent studies, especially the larger study by Yang et al 10,46 strongly support the clinical benefits and indications of cryotherapy for treating HCC, including advanced stage of HCC, in patients with ChildPugh class A or B cirrhosis. However, further studies, especially multicenter studies, are needed to identify the clinical, biochemical, and histologic parameters that help in better selection of suitable HCC candidate patients for best outcomes of cryoablation.…”
Section: Cryoablation For Hccsupporting
confidence: 86%
See 1 more Smart Citation
“…MACC1 was also an independent prognostic factor for colon cancer [3, 5]. Now, more and more studies have demonstrated that MACC1 could also be a metastatic and prognostic factor for various human cancers, including pancreatic [10], liver [11], lung [12], ovary [13], breast [14], gastric [8], malignant glioma [15], and cervical carcinoma [16]. …”
Section: Introductionmentioning
confidence: 99%
“…MACC1 was found significantly upregulated in primary colon cancer and organ metastases compared with normal tissues, indicating that the induction of MACC1 might occur at the crucial step of transition from the benign to the malignant phenotype in the adenomacarcinoma sequence of colorectal cancer (7,9). MACC1 has been described as a prognostic biomarker for tumor progression, metastasis, and survival in different solid tumors (10), including hepatocellular carcinoma (11)(12)(13)(14)(15)(16)(17)(18)(19), gastric (20,21), esophageal (22,23), cervical (24,25), and lung cancer (26)(27)(28). Met was identified as the first transcriptional target of MACC1, suggesting that MACC1 might signal through the HGF-Met pathway to promote tumor growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%